Remote Limb Ischemic Preconditioning Attenuates Cerebrovascular Depression During Sinusoidal Galvanic Vestibular Stimulation via α1‐Adrenoceptor–Protein Kinase Cε–Endothelial NO Synthase Pathway in Rats. Issue 7 (24th March 2018) - McBride, Devin W.; Reis, Cesar; Zhang, John H.; Applegate, Richard; Tang, Jiping
Abstract : Background: Vasovagal syncope (VVS) is characterized by hypotension and bradycardia followed by lowering of cerebral blood flow. Remote limb ischemic preconditioning (RIPC) is well documented to provide cardio‐ and neuroprotection as well as to improve cerebral blood flow. We hypothesized that RIPC will provide protection against VVS‐induced hypotension, bradycardia, and cerebral hypoperfusion. Second, because endothelial nitric oxide synthase has been reported as a mediator of cerebral blood flow control, we hypothesized that the mechanism by which RIPC primes the vasculature against VVS is via the α1 ‐adrenoceptor–protein kinase Cε–endothelial nitric oxide synthase pathway. Methods and Results: We utilized sinusoidal galvanic vestibular stimulation in rats as a model of VVS. RIPC attenuated the lowerings of mean arterial pressure, heart rate, and cerebral blood flow caused by sinusoidal galvanic vestibular stimulation, as well as improving behavior during, and recovery after, stimulation. RIPC induced elevated serum norepinephrine, increased expression of brain α1 ‐adrenoceptors, and reduced brain expression of norepinephrine transporter 1. Antagonizing adrenoceptors and norepinephrine transporter 1 prevented RIPC protection of cerebral perfusion during sinusoidal galvanic vestibular stimulation. Conclusions: Taken together, this study indicates that RIPC may be a potential therapy that can prevent VVS pathophysiology, decrease syncopal episodes, and reduce the injuries associated with syncopal falls. Furthermore, the α1 ‐adrenoceptor–protein kinase Cε–endothelial nitric oxide synthase pathway may be a therapeutic target for regulating changes in cerebral blood flow.